Damage evolution and characterization for sintered powder metals with the varying porosity. (15th February 2019) - Yuan, Huang; Zhang, Long; Ma, Songyun
Highlights: Introduced and verified a multiaxial damage evolution model for porous sintered metals with varying porosity. Established and identified a power-law relation between mechanical property and material porosity. Proposed a prediction model for the fracture strain as function of stress triaxiality and porosity. Illustrated damage mechanisms of the sintered metals depending on the porosity and confirmed the normal fracture as the dominant mechanism for the material failure. Abstract: Micro-structure of sintered powder metals is characterized by the high porosity. Experiments confirm that the major mechanical property can be expressed in a power-law function of the porosity. In the present work the interdependence between the porosity and the elastic-plastic mechanical property as well as the damage evolution in sintered metals with varying porosity is investigated experimentally and analytically. A damage characterization is introduced based on the stiffness degradation to predict the inelastic behavior of the sintered material and the damage process. The proposed damage evolution model is further verified under multi-axial loading conditions.